Human myeloma cell‐ and plasma‐derived extracellular vesicles contribute to functional regulation of stromal cells. Issue 13 (5th March 2021) - Reale, Antonia; Carmichael, Irena; Xu, Rong; Mithraprabhu, Sridurga; Khong, Tiffany; Chen, Maoshan; Fang, Haoyun; Savvidou, Ioanna; Ramachandran, Malarmathy; Bingham, Nicholas; Simpson, Richard J.; Greening, David W.; et al.
Abstract: Circulating small extracellular vesicles (sEV) represent promising non‐invasive biomarkers that may aid in the diagnosis and risk‐stratification of multiple myeloma (MM), an incurable blood cancer. Here, we comprehensively isolated and characterized sEV from human MM cell lines (HMCL) and patient‐derived plasma (psEV) by specific EV‐marker enrichment and morphology. Importantly, we demonstrate that HMCL‐sEV are readily internalised by stromal cells to functionally modulate proliferation. psEV were isolated using various commercial approaches and pre‐analytical conditions (collection tube types, storage conditions) assessed for sEV yield and marker enrichment. Functionally, MM‐psEV was shown to regulate stromal cell proliferation and migration. In turn, pre‐educated stromal cells favour HMCL adhesion. psEV isolated from patients with both pre‐malignant plasma cell disorders (monoclonal gammopathy of undetermined significance [MGUS]; smouldering MM [SMM]) and MM have a similar ability to promote cell migration and adhesion, suggesting a role for both malignant and pre‐malignant sEV in disease progression. Proteomic profiling of MM‐psEV (305 proteins) revealed enrichment of oncogenic factors implicated in cell migration and adhesion, in comparison to non‐disease psEV. This study describes a protocol to generate morphologically‐intact and biologically functional sEV capable of mediating the regulation of stromal cells, and a model for the characterization of tumour‐stromal cross‐talk by sEV in MM.